2016
DOI: 10.1007/s13187-016-1138-7
|View full text |Cite
|
Sign up to set email alerts
|

Using Webinars for the Education of Health Professionals and People Affected by Cancer: Processes and Evaluation

Abstract: Technology provides an opportunity to engage with a variety of audiences to provide cancer education, information and support. Webinars are one such format that allow live presentations by experts that can be accessed online, from people's homes or other convenient locations. In 2015, Cancer Council Victoria (CCV) undertook a program of work to design and evaluate the effectiveness of a suite of webinars: four designed for people affected by cancer and two for health professionals. Webinars included a series o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 3 publications
0
29
0
3
Order By: Relevance
“…The health information seminars were started to shift to online platforms, and the pandemic process is accelerated. The early studies of webinars focus, especially on health professionals' satisfaction and patients' education (2,3). The authors concluded that all learners intended to reduce their own cancer risk.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The health information seminars were started to shift to online platforms, and the pandemic process is accelerated. The early studies of webinars focus, especially on health professionals' satisfaction and patients' education (2,3). The authors concluded that all learners intended to reduce their own cancer risk.…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that all learners intended to reduce their own cancer risk. Patients felt more knowledgeable, prepared, and confident talking about cancer (2,3). For health professionals (HP), the studies generally use the surveys to investigate the results of webinars and showed that HP is satisfied and significantly improved their information, and they would deal with the webinar topics further (3-5).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to its effectiveness, patients favor group learning because it enables them to immediately receive answers to questions, discuss experiences and questions with peers, and experience a feeling of community [ 44 ]. To incorporate group learning during times of social distancing and limited in-person visits, a webinar may be a good option because this delivery mode offers the possibility of synchronous web-based interactive conversation between patients, living donors, and health care providers [ 45 ]. Additionally, contact with peers can increase patients’ self-management, and group education settings can help patients to overcome feelings of isolation [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Even though webinar delivery took less time, it is important to note that both delivery modes took a substantial commitment in terms of recruitment and scheduling of clinics. Delivering email coaching (i.e., 3-and 6-month follow-up Report Cards) also took a lot of time, and might be made more efficient through the use of automated email systems [25]. Trial vaccination coverage analyses are pending; webinar would need to be as effective as in-person coaching for the cost-savings to have practical value to programs.…”
Section: Discussionmentioning
confidence: 99%